Pure Land Buddhism in modern Japanese culture - Porcu, Elisabetta. (Numen Book Series, 2008)
Despite being one of the most influential forms of Japanese Buddhism, the Pure Land tradition, and notably its impact on the development of Japanese cultural history, has often been overlooked outside Japan. Taking into account recent scholarship on orientalism and occidentalism, this book, written from the perspective of the Study of Religions, provides an analysis of the impact that the Pure Land tradition, in particular Shin Buddhism, has exerted on mainstream forms of artistic expression (especially creative arts, literature and the tea ceremony) in modern and contemporary Japan.